\(\displaystyle{\frac{{{\left.{d}{y}\right.}}}{{{\left.{d}{x}\right.}}}}={\frac{{{\left({2}{x}-{1}\right)}{e}^{{{x}}}}}{{{\left({2}{x}+{1}\right)}^{{{2}}}}}}\)

Question

asked 2021-05-30

Find derivatives of the functions defined as follows.

\(\displaystyle{y}={\frac{{{x}^{{{2}}}}}{{{e}^{{{x}}}}}}\)

\(\displaystyle{y}={\frac{{{x}^{{{2}}}}}{{{e}^{{{x}}}}}}\)

asked 2021-05-16

Find derivatives of the functions defined as follows.

\(\displaystyle{y}={\frac{{{e}^{{{x}}}+{e}^{{-{x}}}}}{{{x}}}}\)

\(\displaystyle{y}={\frac{{{e}^{{{x}}}+{e}^{{-{x}}}}}{{{x}}}}\)

asked 2021-06-16

Find derivatives of the functions defined as follows.

\(\displaystyle{y}={\frac{{{e}^{{{x}}}-{e}^{{-{x}}}}}{{{x}}}}\)

\(\displaystyle{y}={\frac{{{e}^{{{x}}}-{e}^{{-{x}}}}}{{{x}}}}\)

asked 2021-06-29

Find derivatives of the functions defined as follows.

\(\displaystyle{y}={e}^{{-{2}{x}}}\)

\(\displaystyle{y}={e}^{{-{2}{x}}}\)